The Effect of Web-Based Interactive Learning Media on Critical Thinking Skills of Elementary School Students - Saputra, Adik Rian; Murti, Rahayu Condro; Hastuti, Woro Sri (Jurnal Prima Edukasia, 2025)
Learning media has an important role in developing students' abilities. However, the use of learning media is still low, especially in developing students' critical thinking skills. This research aims to determine the differences in critical thinking abilities between students who are taught using web-based interactive learning media and classical learning, and the effect of applying web-based interactive learning media on students' critical thinking abilities. It used quasi-experimental research. The research population only consisted of fifth grade students at Sawur Elementary School. In the experimental group the learning process took place using web-based interactive learning media, while in the control group it took place classically. The instruments used are tests that measure students' critical thinking abilities in the cognitive aspect and behavioral scales that measure students' critical thinking abilities in the behavioral aspect. The data was then analyzed using: (1) descriptive statistics to describe critical thinking skills and learning outcomes, and (2) inferential statistics using the Independent Sample t-test and Paired Sample t-test to test the research hypothesis at a significance level of 5% (Î± = 0.05) . The results of the research show that: (a) There is a significant difference in students' critical thinking abilities between the group taught using web-based interactive learning media and the group taught using classical learning and (b) the implementaion of web-based interactive learning media has a positive and significant effect on students' critical thinking skills, with a significance value of 0.005.